THE IMPORTANCE OF PALATAL RELIEF OF UPPER COMPLETE DENTURE - Bayramov, Y.I. (World of Medicine and Biology, 2024)
The purpose of the study was a meticulous visual assessment of the reflection of palatal relief on the outer surface of the prosthesis base. Within the scope of the research objectives, 204 patients (102 men and 102 women) aged 45–90 years old, applying for secondary complete edentulism had not received orthopedic treatment in the last 2 years based on their dental status. During the orthopedic treatment with upper complete dentures for secondary complete edentulism, the improved method was used, and improvements were made in the 2nd and 4th technical stages. The results were comprehensive, with the majority of patients (196 patients, 96.1 %) experiencing the preservation of their sense of taste, satisfactory retention results in 186 patients (91.2 %), and only 7 (3.43 %) reporting minor issues with pronunciation. This thorough research process underscores the reliability and trustworthiness of the findings, and the effectiveness of the improved methods in the treatment of secondary complete edentulism.